The Influence of Consumer Perception Factors on Purchase Intention at YouTube Shopping Affiliate Marketing Platform - Rheza Ivan Farrell; Ira Fachira (Training & Research Institute - Jeramba Ilmu Sukses, 2026)
This study explores the key factors influencing consumer purchase intentions on the YouTube Shopping affiliate marketing platform and how consumer perception of affiliate content on the platform affects purchase intentions. Quantitative approach used by gathering data via a survey of 306 respondents and processed using PLS-SEM through SmartPLS 4.0 software. The results demonstrated that argument quality, expertise, trustworthiness, perceived usefulness, and perceived ease of use had a significant positive impact on consumer perceptions, which, in turn, led to purchase intention. Conversely, entertainment, informativeness, and the static visual cue have an insignificant impact on consumer perception that leads to purchase intention. This study highlights the importance of consumer perception factors (argument quality, expertise, trustworthiness, perceived usefulness, and perceived ease of use) in shaping consumer purchase intentions on the YouTube Shopping affiliate marketing platform. It provides creators with important insights into the factors that significantly improve the effectiveness of their affiliate content on the YouTube Shopping platform